ANALISIS KUALITAS KEUANGAN BANK DAERAH LAMONGAN MELALUI SISTEM PENGENDALIAN INTERNAL (Study pada Bank Daerah Lamongan) - Kusuma Wijaya (Universitas Islam Lamongan, 2018)
This study aims to test empirically : Influence of Human Resources Competence, Internal Control System and Human Resources Competencee through Internal Control System to quality financial report of Bank of Lamongan. This research was conducted at Bank Daerah Lamongan, by using sample of 50 respondents. Data collection method used purposive saampling, while the data analysis technique used is Partial Least Squares (PLS) version 3.2.1.m3, hypothesis testing is done by using outer and iner model in valid data measurement, realibel and feasibel model in determination of dependent variable. The results showed, (1) Human Resource Competence Influential Non-Significant to Quality of PD Bank Regional Report of Lamongan. The higher the Human Resources Competence owned by PD Bank of Lamongan, the Quality of Finance produced by PD Bank Lamongan tend to be better. (2) Internal Control System (SPI) influential Non-Significant to the Quality of Financial Report PD Regional Bank Lamongan. The higher the SPI is implemented, the quality of financial statements produced by PD Bank Lamongan tend to be better. (3) Human Resource Competene Influence Significant to Qulity of Financial Report of Pd Bank of Lamongan Region through Internal Control System (SPI). The higher competence of PD Bank of Lamongan Region through the improvement of SPI application, has an impact on the improvement of Quality of Financial Report of PD Bank of Lamongan Region. Keyword : Financial Quality of Lamongan Regional Bank, Internal Control System, and Human Resource Competence.